Ask a New Question
Search
Questions and answers by
Ellis Others
Answers (2)
Fx Applied = k*x (k=5.8x10^4) Vf=Vo+A(Xf-Xo) Fo=Po*A and Ff=Pf*A Po=kXo/A and Pf=kXf/A Tf=(Pf*Vf*To)/(Po*Vo) Solve for Tf by plugging in the unknown values with the equations above. It would look something like this... Tf=(kxf/a)*(Vo+A(delta
Fx Applied = k*x (k=5.8x10^4) Vf=Vo+A(Xf-Xo) Fo=Po*A and Ff=Pf*A Po=kXo/A and Pf=kXf/A Tf=(Pf*Vf*To)/(Po*Vo) Solve for Tf by plugging in the unknown values with the equations above. It would look something like this... Tf=(kxf/a)*(Vo+A(delta